2008
DOI: 10.1017/s0033291708003723
|View full text |Cite
|
Sign up to set email alerts
|

Associations of C-reactive protein and interleukin-6 with cognitive symptoms of depression: 12-year follow-up of the Whitehall II study

Abstract: Background-A lack of longitudinal studies has made it difficult to establish the direction of associations between circulating concentrations of low-grade chronic inflammatory markers, such as C-reactive protein and interleukin-6, and cognitive symptoms of depression. The present study sought to assess whether C-reactive protein and interleukin-6 predict cognitive symptoms of depression or whether these symptoms predict inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
374
6
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(418 citation statements)
references
References 52 publications
27
374
6
11
Order By: Relevance
“…Conversely, in a cohort of .3,339 participants with .12 years of follow-up, baseline inflammatory marker levels (CRP and IL-6) were associated with a subsequent risk of depression at followup (36). However, this association was not observed in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 86%
“…Conversely, in a cohort of .3,339 participants with .12 years of follow-up, baseline inflammatory marker levels (CRP and IL-6) were associated with a subsequent risk of depression at followup (36). However, this association was not observed in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 86%
“…Some correlational work has found that the relationship between inflammatory markers and symptoms of depression or depressed mood is stronger in males than females (Gimeno et al, 2009;Penninx et al, 2003). Conversely, in the context of clinical studies that follow patients using the cytokine interferon-a (IFN-a), some work has found that females who receive IFN-a are at greater risk of developing depression than males (Gohier et al, 2003;Koskinas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, depressive symptoms have been shown to be associated with increased serum and plasma concentrations of TNF, IL-6 and C-reactive protein (Dowlati et al, 2010;Goldsmith et al, 2016;Strawbridge et al, 2015;Valkanova et al, 2013). Most importantly, recent longitudinal studies have extended these cross-sectional observations by reporting that increased inflammatory markers in non-depressed individuals predict the later development of major depression (Gimeno et al, 2009;Pasco et al, 2010;van den Biggelaar et al, 2007).…”
Section: Introductionmentioning
confidence: 88%